The new encyclopedia britannica in 30 volumes, macropedia VOL.2 / William Benton - Benton, William (1977)
The history of Arizona, the natural and human landscape, the state´s economy, administration and social conditions, cultural life and institutions, the history of Arkansas, the natural and human landscape, the state´s economy, administration and social conditions, cultural life and institution, the military system, the military bureaucracy, the professional soldier, patients of organization, the community